Gustav Davidson papers - Davidson, Gustav, 1895-1971.
Correspondence, writings, research material, biographical material, newspaper clippings, printed material, photographs, and other papers relating chiefly to the Poetry Society of America and Davidson's service as secretary to the society. Includes drafts and published copies of writings including plays, reviews, newspaper columns, and academic writings primarily about angels as well as writings under Davidson's pseudonym W. Gordon Drake. Also includes material from Davidson's travels to the South Sea islands. Correspondents include Charles Angoff, Joseph Auslander, Clarence Raymond Decker, Alfred Dorn, Max Eastman, Harry Meyer Orlinsky, Theodore Roethke, Ernest R. Trattner, and Louis Untermeyer.
Poet, author, and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Angoff, Charles, -- 1902-1979 -- Correspondence; Auslander, Joseph, -- 1897-1965 -- Correspondence; Decker, Clarence Raymond, -- 1904-1969 -- Correspondence; Dorn, Alfred, -- 1929- -- Correspondence; Eastman, Max, -- 1883-1969 -- Correspondence; Orlinsky, Harry Meyer, -- 1908- -- Correspondence; Roethke, Theodore, -- 1908-1963 -- Correspondence; Trattner, Ernest R. -- 1898- -- Correspondence; Untermeyer, Louis, -- 1885-1977 -- Correspondence; Poetry Society of America; American poetry; Angels; Poetry -- Societies, etc; Oceania -- Description and travel; Authors; Poets; Publishers